2017
DOI: 10.1038/ncomms14647
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 restricts T follicular regulatory T cell proliferation through Bcl-6 mediated inhibition of responsiveness to IL-2

Abstract: T follicular regulatory (Tfr) cells control the magnitude and specificity of the germinal centre reaction, but how regulation is contained to ensure generation of high-affinity antibody is unknown. Here we show that this balance is maintained by the reciprocal influence of interleukin (IL)-2 and IL-21. The number of IL-2-dependent FoxP3+ regulatory T cells is increased in the peripheral blood of human patients with loss-of-function mutations in the IL-21 receptor (IL-21R). In mice, IL-21:IL-21R interactions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 70 publications
(125 reference statements)
4
97
0
Order By: Relevance
“…Together with the known importance of IL-2 receptor signaling in the development of KLRG1 + BLIMP-1 hi eTreg cells (17,34), this finding suggests that CD25 − Tfr cells have primarily lost the IL-2-dependent component of eTreg gene expression. We found that ASCL2 may have a role in the down-regulation of CD25; additionally, a recent report has demonstrated that IL-21 signaling in Tregs inhibits CD25 expression via BCL6 (44).…”
Section: Discussionmentioning
confidence: 85%
“…Together with the known importance of IL-2 receptor signaling in the development of KLRG1 + BLIMP-1 hi eTreg cells (17,34), this finding suggests that CD25 − Tfr cells have primarily lost the IL-2-dependent component of eTreg gene expression. We found that ASCL2 may have a role in the down-regulation of CD25; additionally, a recent report has demonstrated that IL-21 signaling in Tregs inhibits CD25 expression via BCL6 (44).…”
Section: Discussionmentioning
confidence: 85%
“…56 The repressor action of IL-21 on Tfr-cell responses was further supported by independent studies. 56 The repressor action of IL-21 on Tfr-cell responses was further supported by independent studies.…”
Section: Others Have Shownmentioning
confidence: 84%
“…IL-21 (secreted by Tfh cells) inhibits Tfr-cell differentiation through IL-21R/STAT3 signaling, maintaining Tfh and Tfr cells regulated by an IL-21-dependent feedback mechanism. 56 Interestingly, higher CD25 expression levels on IL-21R-deficient Tfr cells led to a heightened signaling in response to IL-2. Therefore, IL-2 consumption is required to promote Tfr-cell development.…”
Section: Others Have Shownmentioning
confidence: 99%
See 2 more Smart Citations